Conditional relationship between distress risk and stock returns - Suhee Yun; Jung Min Kim (Global Business & Finance Review (GBFR), 2022)
Purpose: Previous research on the relationship between a firm's distress risk and future stock returns produces inconsistent results. This study attempts to explain the conflicting results of earlier studies by showing that systematic distress risk leads to positive rewards, while unsystematic distress risk leads to low stock returns. In addition, this study intends to elucidate the factors of systematic distress risk and unsystematic distress risk, respectively. In this way, this study informs the rational investor what kind of distress risk they should take. Design/methodology/approach: This study considers two distress-predictor sets to show a possibility between distress risk and stock returns in both directions. The first set includes profitability ratio, excess returns, and volatility, and the second consists of leverage, firm size, and book-to-market ratio. Similar to the methodology proposed in Campbell et al. (2008), this study measures the distress risk using a dynamic logit model. Depending on which explanatory variables predict the distress risk, the relationship between distress risk and future stock returns could be in both ways. Findings: This study first shows that systematic and unsystematic distress risk factors are significant in predicting failures. However, the effects of the two distress risk factors on stock returns appear in opposite directions. Precisely, the systematic distress risk is estimated by the debt ratio, company size, and book-to-market ratio. The common factors of Fama and French (1993) explain the positive risk premium due to the systematic distress risk. In contrast, the unsystematic distress risk is predicted by profitability, momentum effect, and firm-specific volatility. The Fama-French common factors do not explain low stock returns due to unsystematic distress risk. Research limitations/implications: Because of the two different attributes of distress risk, investors must assume systematic distress risk and avoid unsystematic distress risk. Although the results of this study are based on the analysis of the Korean stock market, the main hypotheses can be tested in other countries' stock markets as well. Originality/value: This study is the first to compromise the inconsistent results of existing studies, and it explicitly shows the factors of systematic and unsystematic distress risk.
Keywords: 650; Distress risk; Failure prediction; Fama-French factors; Systematic distress risk